The influence of websites user engagement on the development of digital competitive advantage and digital brand name in logistics startups - Damianos P. Sakas; Dimitrios P. Reklitis; Nikolaos T. Giannakopoulos; Panagiotis Trivellas (European Research on Management and Business Economics (ERMBE), 2023)
Logistics startups gradually rely on digital marketing strategies to acquire a competitive advantage. The main aim of Logistics startups is to increase their digital brand name and user engagement in order to acquire a competitive advantage. To the completion of this target, various digital marketing strategies could be implemented to ensure a differentiating factor. A three-stage data-driven methodology was adopted to evaluate the contribution between the parameters and to reflect strategies that can be presented to improve the website's user engagement and digital brand name. The first part of the study collects data from nine logistics startups' websites over a period of 180 days. The second part of the study employs Fuzzy Cognitive Mapping (FCM) to develop an exploratory diagnostic model that visually depicts the cause-and-effect relationships between the metrics under consideration. In the last part of the study, a predictive simulation model has been created to present the intercorrelation between the examined metrics and to present possible optimization strategies. According to the findings of this study, Logistics startups' websites must be developed with fewer web pages and need to be focused on the customers' target. Additionally, in contradiction with other industries' websites, logistics startups must maintain a steady flow of digital advertisements to optimize brand name and profit.
Keywords: M30; M31; M37; M13; M10; 650; Startups; Competitive advantage; Big data; Brand name